Faktor yang Berhubungan dengan Turnover Intention pada Perawat di RS X Kota Pekalongan - Fatiyah, Sali; Irawan, Teguh; Priharwanti, Ardiana (JURNAL LITBANG KOTA PEKALONGAN, 2023)
Background: Nurses have a very important task for the provision of health services in hospitals. If the existing turnover intention is high, it can be detrimental to the hospital management. Based on data from the HRD Division of X Hospital in 2023, the turnover rate for nurses in 2022 reached 19.23%. The purpose of this study was to determine the factors associated with turnover intention in nurses at X Hospital, Pekalongan City. This type of research is analytic observational research with a quantitative approach using a cross sectional research design. Sampling using saturated sampling. The sample of this study were all nurses who were actively working at X Hospital as many as 30 people. The research instrument used a questionnaire. Data analysis using the Rank-Spearman Correlation Test. The results showed that there was no significant relationship between work stress (? value = 0.545) and turnover intention in nurses at X Hospital and there was a significant relationship between compensation (? value = 0.000), career development (? value = 0.000), and work environment (? value = 0.000) with turnover intention in nurses at X Hospital. Keywords : Turnover intention, nurse, hospital